The analysis of stability of three variants ping-pong protocol to attack of passive interception - Васіліу, Є.В. (Eastern-European Journal of Enterprise Technologies, 2012)
Based on the analysis of eavesdropping attacks on the three variants of the ping–pong protocol the estimations of information leakage depending on probability of attack detection are obtained. It is shown, that the information capacity and security of various variants of the ping–pong protocol are in the inverse proportion.